927. Tap Water Avoidance Decreases Rates of Nontuberculous Mycobacteria in Intensive Care Units. (26th November 2018) - Baker, Arthur W; Smith, Becky; Sexton, Daniel J; Huslage, Kirk; Stout, Jason E; Anderson, Deverick J; Moehring, Rebekah W; Hostler, Christopher; Lewis, Sarah S
Abstract: Background: We recently investigated a clonal outbreak of Mycobacterium abscessus molecularly linked to a colonized water supply at a new hospital addition. Use of sterile water instead of tap water for patient care in ICUs successfully mitigated the respiratory phase of the outbreak. We hypothesized that avoidance of tap water would also be associated with decreased respiratory isolation of other nontuberculous mycobacteria (NTM). Methods: We analyzed all positive cultures for NTM obtained at our hospital from August 2013 through December 2015. The pre-intervention outbreak period was defined as August 2013 through May 2014; the tap water avoidance intervention period was defined as June 2014 through December 2015. NTM isolation was defined as a positive culture from a respiratory specimen obtained from an ICU patient on day 3 or later of hospitalization. We also performed AFB cultures of biofilms obtained from ICU water sources. Results: NTM were isolated from 137 patients during 70, 168 patient-days (figure). NTM isolation decreased from 41.0 patients/10, 000 patient-days in the outbreak period to 9.9 patients/10, 000 patient-days in the intervention period (IRR, 0.24; 95% CI, 0.17–0.34; P < .0001) (table). Incidence rates of the 4 most common NTM ( M. abscessus, M. chelonae/immunogenum, M. avium complex, and M. gordonae ) also markedly decreased. Biofilm cultures were positive for at least 1 NTM isolate in 25 of 33 (76%) ICU water sources, including M. abscessus ( n = 11, 33%), M. chelonae/immunogenum ( n = 11, 33%), and M. gordonae ( n = 11, 33%). Conclusion: The use of sterile water for ICU patient care substantially decreased NTM isolation from patient respiratory specimens, presumably reducing risk of symptomatic infection. Hospitals with endemic NTM should consider tap water avoidance for high-risk patients. Disclosures: All authors: No reported disclosures.